GAMBARAN TINGKAT HEALTH LITERACY PASIEN ULKUS KAKI DIABETIK - Pondaag, Ferlan Ansye (JURNAL KEPERAWATAN, 2020)
Abstract: Low health literacy is one of the factors that cause delays in treatment of diabetic foot ulcers that are not a few people who experience leg amputation of diabetic foot ulcers. The purpose of this study was to describe the level of health literacy diabetic foot ulcers patients in the city of Manado. This research method used is descriptive reaserch. Health literacy was measured by using questionnaires diabetic diabetes literacy and numeracy. Samples were included in the study were 60 people who had diabetic foot ulcers, obtained through purposive sampling technique. Data were analyzed using descriptive method and display in a frequency distribution table. The results showed that there 63,3% participant had marginal diabetic literacy and 73,3% participant had low diabetes numeracy. Conclusion, patients who have limited health literacy tend to experience delays in the treatment of diabetic foot ulcers. Therefore, health workers need to know the level of health literacy when communicating with patients.Keywords: Health literacy, diabetic foot ulcersÂ Abstrak: Health literacy yang rendah merupakan salah satu faktor yang menyebabkan keterlambatan penanganan ulkus kaki diabetik sehingga tidak sedikit penderita yang mengalami amputasi kaki. Tujuan penelitian ini adalah untuk melihat gambaran tingkat health literacy pasien ulkus kaki diabetik di Kota Manado. Metode penelitian ini menggunakan desain penelitian deksriptif. Health literacy diukur dengan mengunakan quesioner diabetic literacy dan diabetes numeracy. Sampel yang ikut dalam penelitian ini sebanyak 60 orang yang memiliki ulkus kaki diabetik, diperoleh melalui teknik purposive sampling. Data dianalisis dilakukan dengan cara deskriptif melihat frekuensi data. Hasil peneltian menunjukkan bahwa 63,3%Â  responden memiliki tingkat diabetic literacy marginal dan 73% responden memiliki diabetes numeracy rendah. Kesimpulan, pasien yang memiliki keterbatasan health literacy cenderung mengalami keterlambatan dalam penanganan ulkus kaki diabetik. Oleh sebab itu petugas kesehatan perlu mengetahui tingkat health literacy ketika memberikan edukasi kepada pasien.Kata Kunci: Health literacy, ulkus kaki diabetic